SEXUAL DIMORPHISM IN PERMANENT MAXILLARY CANINES - GLORIA STAKA; VENERA BIMBASHI (International Journal of Pharma and Bio Sciences, 2013)
The aim of this study was to evaluate the sexual dimorphism in permanent maxillary canines among Kosovo-Albanian population. The study was conducted on 204 dental students, selected from Dental School, Medical Faculty in Prishtina. The mesiodistal and buccolingual diameters of the permanent maxillary canines were measured in dental casts using electronic digital calliper Boss, Germany, which has an accuracy ± 0.01 mm. The descriptive statistics and t-test were calculated. The results showed that in Kosovo-Albanian population mesiodistal and buccolingual diameter of the permanent maxillary canines was larger in males than in females and the difference was statistically significant (p<0.0001). The buccolingual diameters of maxillary canines shoved greater percentage of sexual dimorphism (6.72%) than mesiodistal diameter (3.71%). The study showed that maxillary permanent canines exhibiting significant sexual dimorphism.